Presence of a Distinct S3 Layer in Mild Compression Wood Tracheids of Pinus radiata - Singh, A.P.; Yoon, Soo Kim; Byung, Dae Park; Gap, Chae Chung; Wong, Andrew H.H (Walter de Gruyter, 2003)
A study of electron microscopic evidence for the presence of a distinct S3 layer in mild compression wood tracheids of Pinus radiata was performed. S3 layers have an important role to play in strengthening the xylem tissues in standing trees and in minimizing collapse in wood tissues. These layers are also likely to be an important factor in wood processes involving physical and chemical treatments, as well as in the biodegradation of wood.